Growth Performance Can Be Increased Under High Nitrate and High Salt Stress Through Enhanced Nitrate Reductase Activity in Arabidopsis Anthocyanin Over-Producing Mutant Plants - Lee, Ye Ji; Lee, Won Je; Le, Quang Tri; Hong, Suk-Whan; Lee, Hojoung (Frontiers in Plant Science, 2021)
Nitrogen is one of the most important macro-nutrients for plant growth and crop productivity. The amount of synthetic nitrogen fertilizers supplied to crops has dramatically increased, leading to a notable rise in crop yields. However, excessive nitrogen use has an enormous negative impact on ecosystems and human health through the emission of intense greenhouse gases, such as nitric oxide derived from the nitrate (NO3–) assimilation cascade. Additionally, owing to the development of extensive irrigation in agriculture, crops are known to suffer from high salt stress. The effect of excessive nitrogen fertilizer application has been studied in some crops, but the effect of high nitrate level and salt stress on plant stress tolerance has not been studied in detail. Therefore, in this study we aimed to study the effects of high concentrations of NO3– on salt stress tolerance in Arabidopsis. In addition, since anthocyanin functions as a reactive oxygen species (ROS) scavenger under abiotic stress conditions, we investigated whether enhanced anthocyanin content helps Arabidopsis to withstand higher salt stress levels under high NO3– concentrations by using pap1-D/fls1ko double mutant plants, which accumulate excessive amount of anthocyanin. We found that Col-0 plants are more sensitive to salt stress under high NO3– concentrations. Although both the pap1-D/fls1ko and fls1ko plants accumulated higher anthocyanin levels and radical scavenging activities than Col-0 plants under both normal and salt stress conditions, the fls1ko plants exhibited much better growth than the pap1-D/fls1ko plants. It appears that the enhanced NR activities and transcript levels of NIA1 and NIA2 in pap1-D/fls1ko and fls1ko plants led to an increase in the synthesis of proteins and proline, which increases osmolytes against salt stress. Our results demonstrate that optimal levels of anthocyanin accumulation can enhance growth performance of plants under high NO3– and salt stress conditions.